Factors influencing purchase intention towards smartphone brand among adults in Selangor - Rospata, Mohamad (2017)
The purpose of this study is to investigate the relationship of brand image, product features, price, and peer influence towards purchase intention on smartphone brand among adults in Selangor. A total of 384 questionnaires were distributed using convenience sampling method. However, only 311 set of questionnaire were returned with a response rate of 81.0%. The data collected were analyzed using Statistical Package for the Social Science version 23.0 (SPSS). The reliability analysis, descriptive analysis and inferential analysis were conducted. The reliability analysis score for all variables exceeds 0.6 as suggested by previous researcher except for price. All independent variables are significantly related to purchase intention for smartphone brand among adults in Selangor. The regression model indicated that 53.1% (R2 = 0.531) of the purchase intentions on smartphone brand among adults in Selangor was influenced by all independent variables. Purchase intention on smartphone brand among adults in Selangor is influenced mostly by brand image. Next, the influence factors to purchase intention on smartphone brand among adults in Selangor were followed by product features, perceived peer influence and lastly price. In order to further improve this research, future research should conduct a qualitative research and added a small number of appropriate variables. Knowledge of the factors influencing the intention to buy a smartphone among adults is useful for organizations to prioritize their resources such as investment and time with the most efficient and effective manner.